COULD A PUBLICITY CAMPAIGN FOR EMERGENCY CONTRACEPTION REDUCE THE INCIDENCE OF UNWANTED PREGNANCY AND HOW WOULD WE KNOW IF IT DID - Ziebland, S; Scobie, S (1995)
A campaign to increase knowledge about emergency contraception has been identified as one of the relatively few interventions with the potential to reduce the incidence of unwanted pregnancy. This study relates variations in use of emergency contraception to population characteristics and identifies indicators which may be used to measure the impact of a campaign. The study is a secondary analysis of routinely collected data and health service indicators. Prescription data is used to compare districts and examine the population based factors which are associated with use of emergency contraception and termination of pregnancy. A stepwise multiple regression includes termination of pregnancy rates as the dependent variable. Uptake of prescriptions for emergency contraception and termination of pregnancy rates within FHSAs show a positive correlation (0.56). High use of both services is present in inner London FHSAs. A low termination rate combined with high emergency contraceptive use is typical of West Country holiday locations. Deprivation and the mobility of the young female population explain much of the variance in the termination of pregnancy rate (r=0.76, r squared=0.58). The positive association of terminations and emergency contraception use reflects the (immeasurable) level of unprotected sexual activity in an area, for which indicators such as the mobility and youth of the female population are insufficient surrogates. The effectiveness of campaigns to increase awareness and availability will need to be assessed in the light of this positive relationship with termination rates and the upward trend of emergency contraceptive use.